Avaliação do posicionamento final dos implantes instalados através de guia cirúrgico prototipado comparado com o planejamento virtual - Nigro, Frederico (2010)
The evolution in science and technology gives new procedures to actual Implantology aiming perfectioning of the surgical and prosthetic procedures. Among all evolutions, the highlight is the Surgery Guide that with computed tomography can make virtual planning of the selected implants. With this virtual planning, a guide for prototype is confected and it will transfer the virtual planning to surgical reality, although the precision of those transferences hasn t been evaluated too much. Through the patient s surgeries and with surgical prototype guides, from the virtual planning, implants were installed (24 implants in six patients) and after the end of the surgeries new tomography was made. The new tomography data were inserted in image manipulation program and overlapped to the virtual planning, where can be accomplished mensurations and observe the discrepancies of the measures between the virtual planning and the final surgical reality. The obtained results had an average global deviation of 0,77 ± 0,33 mm of the coronal level of the implant and 1,02 ± 0,61 mm of the apical level with an average variation in degrees of 1,96 ± 0,92º. With these data could be concluded that it has no coincidence between the virtual planning and the final positioning of the implants, in this way, the prosthetics confectioned priorly to the installation of the implants should be avoided, unless it is possible the capture of the cylinders in the prosthetic after the installation of the implants.